Pendekatan Postcolonialism Terhadap Surat Filemon (Merenungkan Kembali Identitas Onesimus Sebagai Budak Yang Melarikan Diri): Merenungkan Kembali Identitas Onesimus sebagai Budak yang Melarikan Diri - Killa, Maikel Enggelo Eden Killa (Jurnal Teologi Pambelum, 2023)
Slavery in the ancient Roman empire was an important reality that contributed to how we interpret the Bible texts that were written at that time. The history of reading Philemon's Epistle has long been colored by interpretations suggesting that Onesimus was a runaway slave who had stolen from Philemon, so he needed Paul to write a letter of reconciliation so that Philemon could receive Onesimus back. However, it turns out that readings like this have direct implications related to the interpretation of colonialism that the "colonizers" are always better than the "colonized," and they are not able to make their own life choices. Therefore, readings like this encourage readers to colonize Onesimus. On the contrary, in this study, the author will try to present the story of Onesimus from another point of view, namely, postcolonial, which opens up a new understanding that Onesimus, as a "colonized," can also make his own life choices and contribute to securing his independence from the security system that has been rooted in the ancient Roman cultural context.